2005
DOI: 10.1021/bm050324l
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Recognition by Imprinting in Semi-Interpenetrating Polymer Network Hydrogel Based on Polyacrylamide and Chitosan

Abstract: Semi-interpenetrating polymer network (semi-IPN) hydrogel was prepared to recognize hemoglobin, by molecularly imprinted method, in the mild aqueous media of chitosan and acrylamide in the presence of N,N'-methylenebisacrylamide as the cross-linking agent. The hydrogel obtained has been investigated by using thermal analysis, X-ray diffraction, differential scanning calorimetry (DSC), and environmental scanning electron microscope (ESEM). Langmuir analysis showed that an equal class of adsorption was formed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 29 publications
6
77
0
1
Order By: Relevance
“…Because of the properties of chitosan and polyacrylamide, several works have explored the feasibility of a polyacrylamide/chitosan blend. These studies have reported different aspects of the characterization, biocompatibility, and release properties of polyacrylamide/chitosan hydrogels [25][26][27]. Synthesis method, swelling kinetics, and Young's moduli for a polyacrylamide/chitosan hybrid polymeric network at various chitosan concentrations, and different swelling media are reported in this work.…”
Section: Introductionmentioning
confidence: 94%
“…Because of the properties of chitosan and polyacrylamide, several works have explored the feasibility of a polyacrylamide/chitosan blend. These studies have reported different aspects of the characterization, biocompatibility, and release properties of polyacrylamide/chitosan hydrogels [25][26][27]. Synthesis method, swelling kinetics, and Young's moduli for a polyacrylamide/chitosan hybrid polymeric network at various chitosan concentrations, and different swelling media are reported in this work.…”
Section: Introductionmentioning
confidence: 94%
“…A frequently used approach to evaluate the selectivity is to calculate the ratio of partition coefficients of the template to that of a template analog. The selectivity is usually calculated from re-binding experiments involving either the template or the analog; data from competition assays is very rare [16,17]. Another quality criterion is the imprinting factor (IF), defined as the ratio of maximum binding capacity values of the MIH to the NIH.…”
Section: Characterization Of Mihmentioning
confidence: 99%
“…Recently, Chen et al [12] imprinted lysozyme within stimuli-responsive network and has shown that the molecular recognition process can trigger changes in molecular interactions that can translate into macroscopic response. However, MIHs imprinted with lysozyme as well as with other proteins often display very low binding capacity of no more than 20 mg protein per gram polymer [12,17,18]. Furthermore, the experimental data presented in the previous publications demonstrate that formulations displaying higher binding capacities tend to be less selective.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan (CS), poly(b-(1,4)-2-amino-2-deoxy-D-glucose), is a hydrophilic polyelectrolyte obtained by the deacetylation of chitin, which is very abundant in nature [19]. CS is a class of cationic polysaccharides containing large number of amine groups together with hydroxyl groups under acidic conditions [20,21]. GPTMS is one of the silane-coupling agents with an epoxy group and three methoxysilane groups [16,17].…”
Section: Introductionmentioning
confidence: 99%